1986
DOI: 10.1111/j.1600-0714.1986.tb00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal breaks and sister chromatid exchanges (SCE) in patients with herpetic stomatitis

Abstract: Zervou-Valvi F, Biizopoulou-Kyrkanidou E, Angelopoulos AP. Chromosomal breaks and sister chtomatid exchanges (SCE) in patients with herpetie stomatitis. .) Oral Pathol 1986: 15: LS 1-154.Chromosomal breakage and sister-chroniatid exchanges (SCE) were studied in peripheral lymphocytes of 9 patients with primary herpetie stomatitis (PHS). 12 patients with secondary herpetie stomatitis (SnS) and 12 controls. The incidence of chromosomal breakage was signifieantly higher in PHS patients (mean 23%, P.=().0()()2) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It has been shown that viruses can cause visible damage to chromosomes of mammalian cells. Increased SCE scores have been found in patients with secondary herpetic stomatitis and with herpetic lesions 35 . Elevated frequencies of SCE have also been reported in peripheral blood lymphocytes of patients with Behcet's disease (BD), 36 ankylosing spondylitis 37 and ataxia telangiectasia 38 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that viruses can cause visible damage to chromosomes of mammalian cells. Increased SCE scores have been found in patients with secondary herpetic stomatitis and with herpetic lesions 35 . Elevated frequencies of SCE have also been reported in peripheral blood lymphocytes of patients with Behcet's disease (BD), 36 ankylosing spondylitis 37 and ataxia telangiectasia 38 .…”
Section: Discussionmentioning
confidence: 99%
“…2000). It has been shown that viruses can cause visible damage to chromosomes of mammalian cells (Zervou‐Valvi et al. 1986).…”
Section: Discussionmentioning
confidence: 99%
“…1986). Elevated SCE scores were found in patients with secondary herpetic stomatitis and with herpetic lesions (Zervou‐Valvi et al. 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations